Blind prediction of homo‐ and hetero‐protein complexes: The CASP13‐CAPRI experiment. Issue 12 (25th October 2019) - Lensink, Marc F.; Brysbaert, Guillaume; Nadzirin, Nurul; Velankar, Sameer; Chaleil, Raphaël A. G.; Gerguri, Tereza; Bates, Paul A.; Laine, Elodie; Carbone, Alessandra; Grudinin, Sergei; Kong, Ren; Liu, Ran‐Ran; et al.
Abstract: We present the results for CAPRI Round 46, the third joint CASP‐CAPRI protein assembly prediction challenge. The Round comprised a total of 20 targets including 14 homo‐oligomers and 6 heterocomplexes. Eight of the homo‐oligomer targets and one heterodimer comprised proteins that could be readily modeled using templates from the Protein Data Bank, often available for the full assembly. The remaining 11 targets comprised 5 homodimers, 3 heterodimers, and two higher‐order assemblies. These were more difficult to model, as their prediction mainly involved "ab‐initio" docking of subunit models derived from distantly related templates. A total of 30 CAPRI groups, including 9 automatic servers, submitted on average 2000 models per target. About 17 groups participated in the CAPRI scoring rounds, offered for most targets, submitting 170 models per target. The prediction performance, measured by the fraction of models of acceptable quality or higher submitted across all predictors groups, was very good to excellent for the nine easy targets. Poorer performance was achieved by predictors for the 11 difficult targets, with medium and high quality models submitted for only 3 of these targets. A similar performance "gap" was displayed by scorer groups, highlighting yet again the unmet challenge of modeling the conformational changes of the protein components that occur upon binding or that must be accounted for in template‐based modeling. Our analysis also indicates that residues in binding interfaces were less well predicted in this set of targets than in previous Rounds, providing useful insights for directions of future improvements.